Good job : success with Aboriginal and Torres Strait Islander employment strategies. - Jones, Gavin; New South Wales. Office of the Director of Equal Opportunity in Public Employment (East Sydney, N.S.W. : Office of the Director of Equal Opportunity in Public Employment, 1994)
Guide to good practice in developing Aboriginal and Torres Strait Islander employment strategies in the New South Wales public sector; with particular focus on Pacific Power, the Department of Courts Administration, TAFE Commission and the University of New South Wales; establishing a strategy; recruitment; training; staff networking.
"Author: Gavin Jones" -- foreword.
Keywords: Aboriginal Australians -- Employment -- New South Wales -- Case studies; Torres Strait Islanders -- Employment -- New South Wales -- Case studies; Civil service -- New South Wales -- Case studies; Aboriginal Australians -- Employment -- New South Wales; Torres Strait Islanders -- Employment -- New South Wales; Education - Vocational and trades; Employment - Labour market; Economic sectors - Manufacturing; Occupations - Public servants; Education - Tertiary; New South Wales (NSW)